Contextualizing HRM in China: differences within the country. Issue 18 (10th October 2016) - Sheldon, Peter; Sanders, Karin
Abstract : Through critical literature review, we introduce the special issue's focus, 'HRM in China: Differences within the country'. Researchers have, in practice, neglected to sufficiently contextualize HRM in China in order to identify, address and explain these differences. This has occurred despite continual calls for better contextualization, a theme common across other, overlapping fields: management in China; organizational behaviour; and HRM in general. A major impediment has been an unwillingness to contextualize beyond the organization or, perhaps the industry. This reflects dominant theoretical preferences in North America that produce literature-led research agendas and 'outside-in' research on China. In effect, academic pressures and the resulting literature also shape research approaches to contextualizing HRM in China. In seeking to promote phenomena-led research with 'inside-out' orientations, we highlight two important contextual conceptions of 'differences': diversity within China, especially where related to space and place; and rising evidence of expressed differences of interests within China's labour markets. The rest of the article provides summary overviews of this special issue's other seven articles, focusing on the phenomena they examine, the contexts they work with, the disciplines they embrace and the research designs/methods they employ. We conclude with suggestions for further research.